Global variations in regolith properties on asteroid Vesta from Dawn's low‐altitude mapping orbit. (22nd September 2016) - Denevi, Brett W.; Beck, Andrew W.; Coman, Ecaterina I.; Thomson, Bradley J.; Ammannito, Eleonora; Blewett, David T.; Sunshine, Jessica M.; De Sanctis, Maria Cristina; Li, Jian‐Yang; Marchi, Simone; Mittlefehldt, David W.; Petro, Noah E.; et al.
Abstract: We investigate the depth, variability, and history of regolith on asteroid Vesta using data from the Dawn spacecraft. High‐resolution (15–20 m pixel −1 ) Framing Camera images are used to assess the presence of morphologic indicators of a shallow regolith, including the presence of blocks in crater ejecta, spur‐and‐gully–type features in crater walls, and the retention of small (<300 m) impact craters. Such features reveal that the broad, regional heterogeneities observed on Vesta in terms of albedo and surface composition extend to the physical properties of the upper ~1 km of the surface. Regions of thin regolith are found within the Rheasilvia basin and at equatorial latitudes from ~0–90°E and ~260–360°E. Craters in these areas that appear to excavate material from beneath the regolith have more diogenitic (Rheasilvia, 0–90°E) and cumulate eucrite (260–360°E) compositions. A region of especially thick regolith, where depths generally exceed 1 km, is found from ~100–240°E and corresponds to heavily cratered, low‐albedo surface with a basaltic eucrite composition enriched in carbonaceous chondrite material. The presence of a thick regolith in this area supports the idea that this is an ancient terrain that has accumulated a larger component of exogenic debris. We find evidence for the gardening of crater ejecta toward more howarditic compositions, consistent with regolith mixing being the dominant form of "weathering" on Vesta.